KOREOGRAFI TARI PIRIANG DANTIANG BALEGO PRODUKSI SANGGAR RUMAH GADANG NAGARI CUPAK, KABUPATEN SOLOK: KAJIAN BENTUK DAN ISI - Nia Putri Jelita; Indrayuda Indrayuda; Nerosti Nerosti (SENDRATASIK UNP, 2018)
AbstractThis article aimed to explain and describe the choreography of Piriang Dantiang Balego dance in the production of Rumah Gadang Studio, Cupak district, Solok Regency. The type of this research was qualitative using descriptive methods. The object of the research was the Piriang Dantiang Balego dance. The data were obtained through direct observation, interviews, and documentation. Data were analyzed based on the Miles and Huberman approach, in the form of data collection, data reduction, data display, and conclusion drawing. The results of the study showed that the Piriang Dantiang Balego dance was a new creative dance that was done with a choreography approach. In the Piriang Dantiang Balego dance, there were choreographic elements such as forms including motion, top design and floor design, group composition, dancers, costumes, dance accompaniment, and dance property. The choreography contents of Piriang Dantiang Balego dance were ideas or notions and the revealed atmosphere through the expression of dancers and dancers' appreciation.Keywords: Choreography and Piriang Dantiang Balego Dance